(untitled) (Research, Society and Development, 2020)
The work of Brazilian public transport drivers has been characterized by situations of vulnerability and high exposure to conditions harmful to the health and safety of workers. The weakening of the union strength over the years has been the subject of several studies, which show concern with the impacts on the phenomenon of precarious work. This study aims to apprehend the perspective of the union and workers regarding the struggle for the health and safety of these workers, in order to demonstrate how the discussion of this aspect takes place in the scope of the negotiations. This is an exploratory-descriptive study with a qualitative approach. The information was collected through semi-structured interviews with union representatives of the Union of Road Workers of Belo Horizonte, in the state of Minas Gerais (Brazil) and public transport drivers from the same city. The analysis revealed that workers are aware of the risks they are subjected to due to their work conditions, and how they negatively impact health and safety. They also express with concern about the increasing difficulty of conquests obtained through collective bargaining. It was perceived with this study the need for collective effort of all - Union, company and Public Ministry, to guarantee the work in adequate conditions, preserving the physical and mental health of the workers. Based on the answers given by union members and workers, several possibilities for debate on the topic are opened, with the perspective of seeking interventions that can improve the work and health conditions of these workers.